Implementasi Program Action Methods (PAM) untuk Meningkatkan Kemampuan Siswa dalam Menyelesaikan Soal Program Linear - Tedy Machmud (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This study was designed to improve students' ability in completing the test refering to the linear program. It focused on the implementation of the Program Action Method (PAM). Applying an action research design, the study involved the third-grader of SMUN I Bolaang, North Sulawesi. The results showed that this implementation of Program Action Method (PAM) managed to improve the students' ability in doing the tests.